Comparative Genetic Analysis of Durum Wheat Landraces and Cultivars Widespread in Tunisia - Miazzi, Monica Marilena; Babay, Elyes; De Vita, Pasquale; Montemurro, Cinzia; Chaabane, Ramzi; Taranto, Francesca; Mangini, Giacomo (Frontiers in Plant Science, 2022)
The durum wheat (Triticum turgidum L. ssp. durum Desf.) landraces constitute a useful natural germplasm to increase the genetic diversity in the modern durum cultivars. The Tunisian durum germplasm constitutes 28 accessions conserved in Genebank of Tunisia, which are still unexplored. In this study, a comparative genetic analysis was performed to investigate the relationships between the Tunisian durum lines and the modern cultivars and detect divergent loci involved in breeding history. The genetic diversity analyses carried out using nine morphological descriptors and the 25K single-nucleotide polymorphism (SNP) array allowed us to distinguish two groups of Tunisian landraces and one of durum cultivars. The analysis of molecular variance and diversity indices confirmed the genetic variability among the groups. A total of 529 SNP loci were divergent between Tunisian durum landraces and modern cultivars. Candidate genes related to plant and spike architecture, including FLOWERING LOCUS T (FT-B1), zinc finger CONSTANS, and AP2/EREBPs transcription factors, were identified. In addition, divergent genes involved in grain composition and biotic stress nucleotide-binding site and leucine-reach repeats proteins and disease resistance proteins (NBS-LRR and RPM) were found, suggesting that the Tunisian durum germplasm may represent an important source of favorable alleles to be used in future durum breeding programs for developing well-adapted and resilient cultivars.